Therapeutic potential of exosomes from adipose-derived stem cells in chronic wound healing - Long, Chengmin; Wang, Jingru; Gan, Wenjun; Qin, Xinchi; Yang, Ronghua; Chen, Xiaodong (Frontiers in Surgery, 2022)
As a thorny medical problem that has received continuous attention in society, chronic wound healing needs to be solved urgently from both anatomical and functional aspects through more efficient ways. Adipose-derived stem cells (ADSCs), mesenchymal stem cells with self-renewal and multiple differentiation capacity, play an essential role in wound healing and tissue regeneration. In addition, exosomes from adipose-derived stem cells (ADSCs‐EXOs) are a sort of extracellular vesicles that serve as an essential means of communication between cells. With various bioactive molecules released, ADSCs‐EXOs can restore tissue homeostasis and accelerate wound healing by promoting various stages of wound repair, including regulating inflammatory response, promoting wound angiogenesis, accelerating cell proliferation, and modulating wound remodeling. Compared with ADSCs, they have the advantage of avoiding ethical issues, being easily stored, and having high stability. In this review, a literature search of PubMed, Medline, and Google Scholar was performed for articles focusing on exosomes from adipose-derived stem cells, chronic wound repair, and therapeutic potential prior to 1 August 2022. This review aims to provide new therapeutic strategies for more investigators to explore how ADSCs‐EXOs regulate intercellular communication in chronic wounds.